Techno-Economic Analysis and Optimization of a Fischer–Tropsch Microreactor for Synfuels Production from Unconventional Feedstocks - Mamabolo, Botang (University of the Witwatersrand, Johannesburg, 2024)
The Fischer-Tropsch (FT) process has been applied in the petrochemical industry since its initial development in the early 20th century – allowing for the conversion of carbon-rich resources into liquid fuels and chemicals. Micro-FT (Fischer-Tropsch) reactor systems are an adaptation of the FT process for application in the micro-scale. Micro-FT reactors have the potential to unlock natural resources that have thus far been overlooked. Given this, a thorough comprehension of the governing mechanisms in these systems is important. This has been lacking mostly because of the relative novelty of the concept in FT reactor applications. FT microreactor models represent the operation of FT synthesis at a microscale, where the reactor's dimensions are typically in the range of micrometers to a few millimeters. This small scale can significantly enhance mass and heat transfer rates, leading to more efficient reactions. Reliable micro-FT reactor physical models, able to describe the physical characteristics and behaviour within the micro-reactor, are not openly available in literature and those that are accessible are not comprehensive. While these FT microreactor models offer some insight into micro-FT physico-chemical processes such as hydrodynamics and kinetics, they often depend heavily on simplistic assumptions and this loses the complexity of the real process and renders the model inaccurate. In addition to the technical challenges, the economics related to the commercial viability of a micro-FT driven GTL plant are crucial. The economics associated with micro-FT reactor application must be favourable if this technology is to be adopted. The challenge is the lack of economic models to enable the determination of this viability. The problems around the micro-FT reactor are therefore two-fold, including the technical issues around the reactor model and optimal manifold design and economic issues regarding the methodology applicable in determining the economic feasibility of a mini- GTL plant using micro-FT technology. To solve the current problems outlined above, a holistic approach to the study of the micro-FT system was adopted where the technical and economic aspects were explored to improve the understanding of micro-FT reactors through a comprehensive study and analysis of the reactor and its economic implications. The FT microreactor offers several advantages over conventional FT reactors including enhanced heat and mass transport rates because of the miniature size of the channels and these ultimately lead to a more efficient reactor system. The principles governing the behaviour of a three-phase one- iv dimensional 2-bubble-class microchannel system were analysed based on those of a similar, albeit larger FT reactor in the form of a slurry bubble column reactor (SBCR). An FT microchannel reactor mathematical model was developed from 1st principles based on the mass conservation law which was applied to three distinct compartments including the large bubble, small bubble and liquid phases. The model was found to be capable of describing the fate and behaviour of the reactants, more specifically the CO across the length of the microchannel. It was determined that two key parameters primarily influence the performance of the microchannel reactor including the total superficial gas velocity and the axial dispersion, particularly in the gas phase. An increase in the superficial gas velocity from 0.0018 to 0.309 m/s, was found to enhance axial dispersion in both liquid and gas phases by 99.9% and 78.7% respectively and increase large bubble hold-up from 0.015 to 0.158 resulting in the net effect of a reduced syngas conversion from 70% to 40%. It was also determined that an increase in the microchannel diameter from 2.6 𝑥10-3 to 3.4𝑥10-3 m resulted in an increase in overall syngas conversion from 30% to 70% conversion through its obvious effect on residence time but also indirectly through its influence on the dispersion in the large bubble compartment. The solids concentration (0.38 – 0.3825 v/v) was found to enhance the syngas conversion up to a point (𝐶௏=0.3825), beyond which the effect of the decreasing small bubble hold-up (75% decrease) outweighs the improved reactant consumption rate. Increasing the temperature between 470 K and 515 K was found to improve the reaction kinetics and reduce the large bubble axial dispersion which had the net result of improving syngas conversion by 46.6%. The model results were compared with the results from literature experiments conducted under similar conditions. It was found that the two sets of results are reasonably similar. The capital cost estimate of a mini-GTL plant, using an FT microchannel reactor, was found to be 95% lower than that from a conventional size GTL plant. More importantly, the cost/bbl estimate for the mini-GTL case was found to be 33% lower than in the conventional size case as a result of the improved efficiency brought about in large part by the FT microreactor unit.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy , in the Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Fischer-Tropsch; Micro-reactor; Hydrodynamics; Mathematical Modelling; Simulation; Chemical Engineering; Oil & Gas; SDG-7: Affordable and clean energy; SDG-9: Industry, innovation and infrastructure